Cerebrotendinous Xanthomatosis. Report of a case in Peru: Comprehensive clinical evaluation and neuroimaging studies. - Castañeda, Marco A. (2019)
The case of a 73 years-old woman that, since approximately the age of 30 years started to complain of pain when walking, is presented. The symptom was mainly located in the acchillean regions which, as time advanced, showed gradual volume increase and, finally, forced her to seek medical evaluation. Accompanying relatives reported a several years history of gradually increasing cognitive difficulties (i.e., forgetfulness, disorientation, poor attention and concentration), fluctuating mood (from periods of good humor switching to sudden episodes of sadness and crying spells), emotional lability and anxiety crises evolving into brief panic attacks. The Mini-cognitive Fenton Test confirmed severe dementia and the neurological evaluation showed cerebellar ataxia and partial pyramidalism. The ophthalmological examination revealed xanthelasmas, cataracts and dense arcus senilis. Xanthomas were detected in the Achillean tendons of both lower extremities. Auxiliary laboratory and densitometric tests demonstrated mixed dyslipidemia and dorsal-lumbar osteoporosis, respectively, and magnetic resonance imaging of the brain (RMC) confirmed SNC damage and suggested deposits of cholestenol, thus confirming the diagnosis of Cerebroitendinous Xanthomatosis.